Modeling digital health systems to foster interoperability - Oemig, Frank; Blobel, Bernd (Frontiers in Medicine, 2022)
Information systems are a complex thing, and they are mostly not used stand-alone anymore. In that context, many different issues must be considered. It starts with defining the system's purpose, includes the use cases and scenarios in combination with the necessary data ideally separated into distinct domains. Furthermore, it requires the selection of an appropriate set of supporting components/tools and a development environment including some technology to enable continuous integration. And the endeavor does not come to an end with the development of the system itself. To manage those challenges, thinking about design and architectural principles becomes a mandatory element. The situation gets more complicated with growing expectations regarding communication and cooperation between the more and more complex and dynamic ecosystem's actors. The resulting information system has to adhere to different, sometimes contradictory principles and requirements, frequently controlled by different authorities. This paper focuses less on developing information systems in general but concentrates on the aspects that must be considered when multiple requirements from different stakeholders for data exchange and knowledge sharing for advanced interoperability must be met. The latter is commonly underspecified due to missing proper verification of the correct interpretation of data. One intent of the paper is to promote the deployment of information models as a common basis to derive data exchange specifications establishing advanced interoperability. However, it also addresses the necessity to guarantee that the information models and implementable artifacts correctly represent the intended functions and objectives as well as the underlying concepts of the business system in its prevailing context. Therefore, we cannot limit our considerations on the data and information viewpoints.